Risks and Threats to Russia’s Food Security: the Current Situa-tion and Tools for Remedying it - G. Reshetnikova, E.; V. Reshetnikova, N.; D. Iosipenko, V. (International Journal of Engineering and Technology, 2018)
This paper provides a rationale for the need to enhance the system of institutions concerned with ensuring food security in a climate of implementation of a strategy of import substitution. The authors examine a set of key factors that can affect the sustainable development of Russiaâ€™s agri-food complex and give rise to threats and risks to the nationâ€™s food security. The paper provides an assessment of the current level of the nationâ€™s physical and economic accessibility of food, traces the role of the small agri-business sector, and analyzes the factor of interregional trading barriers in ensuring food security. The authors demonstrate the advisability of cultivating multiformat food retail and developing various forms of food wholesale. The paper provides a rationale for the need to implement a program of internal food assistance to help overcome social risks to food security and stresses the importance of government support for the participation of small retail and agri-business formats in it.Â Â Â